Human Papillomavirus and Cervical Dysplasia in Latinas: Evaluating the Association Between HPV Infection and Cervical Dysplasia [A99]. (May 2022) - Fanucchi, Hannah; Naresh, Amber
Abstract : INTRODUCTION: Given the elevated risk of cervical dysplasia and malignancy in the Latina population, we sought to assess the rate of high-grade cervical dysplasia in a population of Latina patients with human papillomavirus (HPV)-positive testing on screening Pap smear, relative to a non-Latina White population. We additionally assessed rates of HPV vaccination, HPV strains, and concordance of cytology/histology. METHODS: We conducted a retrospective chart review of all HPV-positive patients undergoing colposcopy across three clinics (January 2019 to September 2021), comparing demographic factors, medical history, cytology, HPV strains, and histology results between the groups. Logistic regression was performed to control for potential confounding factors. RESULTS: We identified 164 patients with positive HPV testing on Pap smear who completed histologic evaluation. No difference was seen in age, immunosuppression, prior abnormal Pap smears, or cytology between Latina and non-Latina patients. CIN2+ was identified in 57.6% of Latina patients, compared to 22.5% among non-Latina White individuals; P <.001. The significant difference persisted when controlling for tobacco use, HPV vaccination, immunosuppression and history of abnormal Pap smear. Latinas had less concordance between cytology and histology: 45.7% of Latinas had CIN2+ after initial low-grade cytology, compared to 7.7% of non-Latinas; P <.001. CONCLUSION: Among HPV-positive patients, Latina ethnicity was associated with increased risk of high-grade cervical dysplasia relative to non-Latina patients, despite no difference in initial cytology or other relevant medical factors. Latina ethnicity was additionally associated with lower HPV vaccination rates and decreased concordance of cytology and histology, with a higher rate of high grade histology following low-grade cytology.